Case Report: PET-CT ischemia and viability maps guiding an emergency revascularization - Adamopoulos, Dionysios; Meyer de Stadelhofen, Léo; Mach, François; Garibotto, Valentina; Noble, Stéphane (Frontiers in Cardiovascular Medicine, 2025)
A 60-year-old woman was scheduled for elective coronary angiography after a positron emission tomography and computer tomography (PET-CT) cardiac perfusion imaging test showing extensive myocardial ischemia. A few hours before the scheduled angiography, she presented to the emergency room with chest pain and diffuse ST-segment modifications leading to emergent coronary angiography. Recent PET-CT ischemia and viability maps were available at the time of the intervention, favoring a percutaneous coronary intervention for chronic total occlusion (CTO PCI) of the left circumflex artery, apart from the culprit lesion of the left main coronary artery and left anterior descending artery, with good results. A second PET-CT scan 23 days post-PCI showed a reversible perfusion defect of the first diagonal branch territory, which was subsequently treated. A rapid normalization of the left ventricular ejection fraction (LVEF) was noted after revascularization, while the second PET-CT showed no signs of significant myocardial necrosis. This case illustrates the potential role of cardiac imaging perfusion studies in guiding revascularization in complex cases in the context of an acute myocardial infarction (MI).